Art and Cultural Diversity of Dayak Ngaju Tribe: Christian Education Interactive Learning on Kuala Kurun - Sugiyanto Sugiyanto; Alfonso Munte (Universitas Negeri Medan, 2024)
The prevalence of comedy and satirical programming on television and online platforms has contributed to a growing divide between entertainers (musicians) and their audiences, with the former offering guidance, criticism, and a reflection of everyday life through their work. As far as the researchers's search and exploration, there are still a few who examine and can even be said to rarely relate music through the culture of Karungut and Deder song, a culture that exists and lives in Dayak Ngaju, Central Kalimantan. This research is interesting because besides music as a fun strategy, Deder song as local wisdom is an expression of the daily life of the Dayak people in Central Kalimantan. This song contains advice, satire, advice and is still present today as part of the richness of world civilization. Lantunan Deder is presented in traditional events (weddings, welcoming guests and various Manasai dances that include men and women in rhythm or balance). Participation in Lantunan Deder has become interesting as a strategy for learning about the content of Christian religious education lessons in schools, living rooms and churches. The usefulness is more about the love of culture, God also sensitizes the participation of women and men as part of the sustainable development goals (SGDs). The research method used 4D model development with analysis and validation space and considered diversity, and song structure. The results showed that Deder as method, strategy, development, cultural actualization, as well as an instrument rarely done in the learning process of Christian religious education and researchers conducted direct practice in the field by melting Deder chants with the learning process which resulted in the creativity of students as actors and user subjects as well as cultural preservation subjects for Ngaju Dayak culture.